The Role of Insulin, Insulin Growth Factor, and Insulin-Degrading Enzyme in Brain Aging and Alzheimer's Disease - Claude Messier; Kevin Teutenberg (Neural Plasticity)
Most brain insulin comes from the pancreas and is taken up by the brain by what appears to be a receptor-based carrier. Type 2 diabetes animal models associated with insulin resistance show reduced insulin brain uptake and content. Recent data point to changes in the insulin receptor cascade in obesity-related insulin resistance, suggesting that brain insulin receptors also become less sensitive to insulin, which could reduce synaptic plasticity. Insulin transport to the brain is reduced in aging and in some animal models of type 2 diabetes; brain insulin resistance may be present as well. Studies examining the effect of the hyperinsulinic clamp or intranasal insulin on cognitive function have found a small but consistent improvement in memory and changes in brain neuroelectric parameters in evoked brain potentials consistent with improved attention or memory processing. These effects appear to be due to raised brain insulin levels. Peripheral levels of Insulin Growth Factor-I (IGF-I) are associated with glucose regulation and influence glucose disposal. There is some indication that reduced sensitivity to insulin or IGF-I in the brain, as observed in aging, obesity, and diabetes, decreases the clearance of Aβ amyloid. Such a decrease involves the insulin receptor cascade and can also increase amyloid toxicity. Insulin and IGF-I may modulate brain levels of insulin degrading enzyme, which would also lead to an accumulation of Aβ amyloid.